Implementación de un receptor GPS utilizando dispositivos de bajo costo para la decodificación de información satelital del sistema de posicionamiento global - Veloz Vallejo, Cristian Andrés (2022)
This research project presents the "Implementation of a GPS receiver using low-cost devices for decoding satellite information of the Global Positioning System," which aims to decode the ephemeris emitted by satellites by designing a GPS receiver based on low-cost development cards. The Ublox NEO-6M receiver used for the research performs error correction in real-time; this eliminates several sources of error such as Atmosphere, receiver, multipath effect, and imprecision in clocks making it more accurate than other devices. The outlined objective achievement of a review of books, articles, magazines, and thesis for the development of the theoretical framework and, in addition, applied research was carried out for the prototype design based on the technological findings of the documentary research. This project was initially developed with signal reception in two different scenarios and a trajectory of 10 points each to identify the accuracy demonstrating it with an analysis of the distance at each end. A comparison of the performance that the prototype has based on a commercial topographic GPS and a handheld one, the actual coordinates were obtained from the Military Geographic Institute to make the comparison with the ASHTECH 10 equipment, Xiaomi and Ublox Neo 6M GPS, and perform the data processing with the calculation of the absolute error of the distance between two geographical coordinates, and finally the Analysis of Variance, in which the null hypothesis is approved, which determines that the Raspberry has an error considered about the rest. Therefore, the designed device has better accuracy compared to the devices mentioned above.